Potential factors that can affect the performance of undergraduate pharmacy research students: a descriptive study - Danijela Gnjidic; Narelle da Costa; Nial J. Wheate (BMC Medical Education, 2023)
Abstract Objective This descriptive study aimed to examine whether student past coursework performance, student or research supervisor characteristics, and the type of research project are related to the overall academic performance of a pharmacy student completing an honours research program. Methods Data on undergraduate honours students who completed a Bachelor of Pharmacy degree at The University of Sydney, Sydney, Australia, between Jan 2015 and Dec 2020 was collected. This included socio-demographic characteristics, type of project undertaken, and academic outputs. Data was also collected on each supervisor’s academic role, level of experience, research area, and where they completed their PhD. Descriptive statistics were used to describe the study cohort and correlation analysis and unpaired t-tail analyses were conducted using SPSS software. Results This five year study included 130 students of which 67% were female and 60% were domestic students. Each student was supervised by one of 48 individual academics who were a mix of early- (31%), mid-career (29%), and experienced researchers (40%) for pharmaceutical science (50%), clinical (45%), and education (5%) projects. Just less than half (49%) of students published one peer-reviewed journal article. Female students outperformed male students (p = 0.031) with female students also twice as likely (15%) to receive a university medal eligible mark compared with male students (7.0%). Similarly, domestic students were twice as likely (15%) to receive a university medal eligible mark when compared with international students (7.7%). Students who undertook a pharmaceutical science-based project outperformed education-based project students (p = 0.0235). Students who had published at least one peer-reviewed journal article outperformed those who had not published (p = 0.0014). Conclusion Factors that affected honours performance were student gender, residential status, type of project undertaken, and whether a student had published a peer-reviewed journal article.